JEAN-LUC NANCY AND THE FRACTAL ONTOLOGY OF NATURE. - Larios, Joe (Cosmos & History, 2024)
This paper seeks to elucidate an affinity between fractal geometry and the ontology of Jean-Luc Nancy. I argue that Nancy's notion of being singular plural, whereby each being is defined as a circulating play of other beings exposed to one another in the space of a sheer opening--what he calls "being-with" or the spacing that allows for beings to be together and relate to one another--provides a description of existence which is both ecological and fractal. It is ecological inasmuch as every being now appears as a temporarily cohering system based on stable networks of circulation thus marking them as fundamentally processual and temporal rather than substantive. It is fractal insofar as each being appears as a composite of a circulation of other beings who, themselves, are also composites of other circulating beings and so on and so forth both up and down scale levels. To substantiate these points, Nancy is brought into conversation with Mandelbrot and the different ways in which fractals have been used to model ecological phenomena to show that these two descriptions are consonant with one another. Moving from the significance of how a fractal is defined as a certain kind of roughness and excess within geometric space to the importance of, specifically, self-affine fractals in the modeling of natural formations like mountain ranges to the aggregations of Brownian motion, this paper seeks to elaborate upon a fractal ecology of nature by way of Nancy and Mandelbrot.